Value Engineering Of Modern Formwork In Multi-Story Building Construction Case Study On The Construction Project Of The Brin Building Complex In Yogyakarta - Dewangga, Rezha Tanu; Suryani, Fitri; Nurjaman, Hari Nugraha; Dinariana, Dwi (Green Publisher Indonesia, 2024)
Reinforced concrete is the most commonly used construction material in building construction in the 21st century. In its production, supportive instruments are needed to enhance both quality and economic aspects. Formwork, or shuttering, is a crucial factor in the casting and hardening of concrete. The subject of this research is wooden formwork and its alternatives, analyzed in terms of cost, quality, time, and convenience using the Value Engineering Job Plan analysis. In terms of cost, there is a cost savings of 8.88% for DUO polymer formwork compared to the conventional plywood method. The resulting surface quality of the concrete of this method has a average roughness of 3.492. The total duration of the work is 16.54791 days. The total value index obtained for the use of DUO polymer formwork is 98.99, for the plywood film formwork is 48.17, and for conventional plywood formwork is 0.00. Thus, in terms of value, the DUO polymer plastic formwork can be recommended as the best formwork method for multi-story building construction. Considering the advantages and disadvantages of this method, along with the benefits obtained, it would be even more beneficial on a larger construction scale.